Plan de mercadeo para la maestría en ingeniería agroindustrial de la Universidad Nacional de Colombia sede Palmira (2020)
The purpose of this document is to design a Marketing Plan for the promotion of the master's program in agribusiness of the National University of Colombia, Palmira headquarters, to develop this structure some aspects related to the research topic are raised, then the problem is described and formulated; setting a general objective and specific objectives. By means of a bibliographic analysis the referential framework will be proposed, establishing a scope and defining the limits of the work by means of a quantitative methodology, the internal and external analysis and diagnosis will be carried out; Subsequently, select strategies and an action plan to finally reach some recommendations and conclusions regarding the project.